Trust or money? Barriers to health and healthcare behavior during the COVID-19 pandemic - Rudisill, Caroline; Linvill, Katie; Chupak, Anna; Costa-Font, Joan; Harrison, Sayward; Hung, Peiyin; Li, Xiaoming (PloS one, 2025)
This study aimed to examine how trust in institutions and changes in household finances were associated with healthcare utilization and preventive behaviors during and immediately after the COVID-19 pandemic. The COVID-19 pandemic worsened health disparities, ignited distrust in healthcare systems, and contributed to household economic shifts for many United States (US) residents. To examine these issues, we surveyed a nationally representative sample of US residents in July 2020 (n = 1,085) and May 2023 (n = 2,189). These repeated cross-sectional surveys enabled investigation of how trust in key stakeholders (e.g., federal government, the healthcare system) and household finances were linked with various types of healthcare utilization (e.g., annual preventive visits, receipt of pharmacy-based healthcare), preventive health care (e.g., influenza vaccination), and preventive behaviors (e.g., exercise, healthy eating). In 2023, the likelihoods of using some types of healthcare (annual health check and pharmacy-based healthcare) and engaging in preventive health behaviors increased relative to 2020. Improved household finances were associated with greater odds of healthy eating, exercising, and receiving annual preventive visits. Trust in the healthcare system was positively associated with all healthcare use types examined including preventive care such as influenza immunization and the individual prevention behavior of healthy eating but not exercise. Findings highlight the important role healthcare systems can have as trusted entities in potentially supporting healthcare utilization and prevention in the post-pandemic environment. Policy implications of these findings include increased efforts by payers and healthcare systems to facilitate positive health behaviors for US residents via specific strategies, such as making annual preventive health checks more accessible. At the same time, it is critical to support maintaining and building trust in healthcare systems to promote appropriate healthcare utilization.